ERADICATION OF WILD LEVELS IN PUBLIC SERVICES IN BANDUNG CLASS I ROUTINE - Umar Anwar (Polteknik Ilmu Pemasyarakatan, 2018)
Illegal levies have been ingrained in the correctional ranks that exist throughout Indonesia. This has become a bad precedent for socialization in the community. With this, it is necessary to improve the integrity and transparent public service system that is provided to service recipient communities to improve public trust in correctional services in prisons and detention centers in Indonesia. Services that can be provided to service recipient communities are services that can be seen directly from the results and transparency in realizing excellent service and quality. Services that are a complaint against indications of illegal levies in prisons and detention are services to visits (bezel), remission proposals, assimilation, conditional leave, free explanatory leave, paid release, and the provision of other services needed by the community and prisoners. To get information that is as clear as possible, this study uses descriptive qualitative research methods by measuring the behavior of officers, prisoners, and prisoners. The research uses in-depth interview methods to visitors (bezel), to prisoners and prisoners as data sampling and direct observation in the Class I Prison in Bandung to find out the actual conditions in the research locus. The results of the study indicate the need for strengthening commitment with all levels of officials and officers in the Bandung Klas I Prison in eradicating illegal levies in providing services, increasing commitment and integrity in services, providing Information technology-based services and strict supervision of the giving of prisoners' rights. Realizing principles and regulations are necessary to provide guidance and training for all Klas I Bandung detention officers to strengthen Integrity in the implementation of tasks. With training and education can provide strength and insight for officers to be able to build integrity and commitment to good service in prison.